The Relationship Between the Fear of Contracting Coronavirus and the Holiday Purchase Intention of Employees Working in Public Institutions - Doğan, Yunus; Buyruk, Lütfi; Balikçioğlu Dedeoğlu, Sevgi; Ercik, Cevat (Anais Brasileiros de Estudos Turísticos, 2022)
The current study aims to determine the relationship between the fear of contracting the coronavirus, the uncertainty levels related to the coronavirus, the anxiety levels related to the coronavirus and the holiday purchase intention of the employees working in public institutions. To achieve this goal, 372 employees from Social Security Institution of Ankara were contacted, and data was collected using a survey technique. The model built within the scope of the research was tested using the partial least squares (PLS) approach. According to the findings of the research, public employees’ fear of contracting the coronavirus is strongly impacted by both their uncertainty about the coronavirus and their anxiety level about the coronavirus, whereas their purchase intentions are only adversely affected negatively by their anxiety levels about the coronavirus. Keywords: Covid 19; Fear of Contracting Coronavirus; Holiday Purchase Intention.